Analisis Penerapan Pembiayaan Gadai Emas Dan Pembiayaan Mikro Di Bank Syariah Indonesia (Bsi) Kcp Gunung Tua - Nurhasanah Siregar; Siti Aisyah (Jurnal Mirai Management, 2023)
Financing is the provision of capital by financial parties to parties in need of funding to operate a firm. Most MSMEs manage their enterprises with their own capital and have little access to formal financial resources. Gold collateral financing is a financing product provided by Islamic banks for the purposes of consumption and production activities with a contract murabahah/Musharakah Mutanaqishah/Ijarah with gold collateral associated with the contract. Rahn, then the bank will maintain the guarantee. a certain period of time. This study attempts to comprehend Bank Syariah Indonesia's function in the company growth of MSME clients. In this study, interviews and observational documents were utilized to collect data. The type of research used was qualitative research. The study's findings demonstrated the significance of Keywords: Microfinance, Gold pawn financing, MSMEs, Bank Syariah Indonesia KCP Gunung Tua.